Islamic Educational Values in the Verses of the Song “Mars Nahdlatul Wathan” by TGKH. Muhammad Zainuddin Abdul Madjid from Lombok - Ulyan Nasri; Muzakkir Walad; Muhammad Zainul Ansori (ASTEEC, 2023)
This research aims to analyze the Islamic educational values embedded in the verses of the song